2019
DOI: 10.1021/acs.est.8b05024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biochar on Microbial Growth: A Metabolomics and Bacteriological Investigation in E. coli

Abstract: Biochar has been proposed as a soil amendment in agricultural applications due to its advantageous adsorptive properties, high porosity, and low cost. These properties allow biochar to retain soil nutrients, yet the effects of biochar on bacterial growth remain poorly understood. To examine how biochar influences microbial metabolism, Escherichia coli was grown in a complex, *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 74 publications
3
43
0
Order By: Relevance
“…The toxicities of biochar to soil biota and aquatic organisms were heavily reported through the avoidance behavior bioassay, assessing survival rates, vertical distribution, weight changes, superoxide dismutase (SOD) activity and protein content for soil biota, and assessing inhibition rates and lethality percentages for aquatic organisms (Liang et al 2019b;Prodana et al 2019;Zhang et al 2019b). A key insight into gene-environment interactions was also conducted to assess the toxicities of biochar to soil microbiota by metabolomics investigation (Hill et al 2019). The toxicities of biochar were largely dependent on raw materials, pyrolysis temperature, and particle sizes of biochar (Liu et al 2019;Prodana et al 2019;Zhang et al 2019b, c).…”
Section: Biochar Productionmentioning
confidence: 99%
“…The toxicities of biochar to soil biota and aquatic organisms were heavily reported through the avoidance behavior bioassay, assessing survival rates, vertical distribution, weight changes, superoxide dismutase (SOD) activity and protein content for soil biota, and assessing inhibition rates and lethality percentages for aquatic organisms (Liang et al 2019b;Prodana et al 2019;Zhang et al 2019b). A key insight into gene-environment interactions was also conducted to assess the toxicities of biochar to soil microbiota by metabolomics investigation (Hill et al 2019). The toxicities of biochar were largely dependent on raw materials, pyrolysis temperature, and particle sizes of biochar (Liu et al 2019;Prodana et al 2019;Zhang et al 2019b, c).…”
Section: Biochar Productionmentioning
confidence: 99%
“…On other hand, the addition of biochar at a rate of 2.5% appear not reduce E. coli during the 85 days of experiment (Table 2), agreeing with Soares et al [18] who reported a marked decrease in CFU mL −1 for survival of E. coli by the storage period (90 days) and not by the addition of biochar at a rate of 4.5% to cattle slurry. However, recent studies [24,25] suggest that the presence of biochar influences the removal of E. coli and minimizes the impact on bacterial viability, which requires further research.…”
Section: Composition Of the Slurriesmentioning
confidence: 99%
“…Scientists all over the world have studied Escherichia coli and it appears to be the most thoroughly investigated and best understood of all model microorganisms [ 1 , 2 , 3 , 4 ]. We already know that it is one of the first bacteria that colonizes the human gut immediately after birth [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%